2015
DOI: 10.1177/0363546515608161
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Anterior Cruciate Ligament Reconstruction in a Dry Model

Abstract: These models may be used to ensure a minimal level of competence before residents and fellows perform ACLR in the operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The studies were broadly split into 3 categories: studies measuring the impact of a simulation training intervention (26 studies 6 - 31 ), studies assessing the construct validity of a simulator designed for training surgeons (42 studies 32 - 73 ), and studies validating an assessment tool (37 studies 74 - 110 ) (see Appendix Tables 1 and 2, column 1). Of the included studies, 60% assessed arthroscopic skill involving the knee (34 studies) 6 , 8 , 9 , 13 , 15 , 17 , 19 , 31 - 33 , 36 , 38 , 39 , 41 , 42 , 47 , 48 , 54 - 56 , 63 , 74 , 75 , 77 - 83 , 86 , 87 , 89 , 91 , the shoulder (25 studies) 7 , 12 , 15 , 16 , 18 , 20 , 37 , 40 , 44 , 45 , 49 , 51 , 53 , 54 , 56 , 63 , 76 , 77 , 81 , 82 , 88 , 90 - 92 , 110 , the hip (3 studies) 43 , 50 , 85 , the ankle (1 study) 14 , and basic general arthroscopic skills (6 studies)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were broadly split into 3 categories: studies measuring the impact of a simulation training intervention (26 studies 6 - 31 ), studies assessing the construct validity of a simulator designed for training surgeons (42 studies 32 - 73 ), and studies validating an assessment tool (37 studies 74 - 110 ) (see Appendix Tables 1 and 2, column 1). Of the included studies, 60% assessed arthroscopic skill involving the knee (34 studies) 6 , 8 , 9 , 13 , 15 , 17 , 19 , 31 - 33 , 36 , 38 , 39 , 41 , 42 , 47 , 48 , 54 - 56 , 63 , 74 , 75 , 77 - 83 , 86 , 87 , 89 , 91 , the shoulder (25 studies) 7 , 12 , 15 , 16 , 18 , 20 , 37 , 40 , 44 , 45 , 49 , 51 , 53 , 54 , 56 , 63 , 76 , 77 , 81 , 82 , 88 , 90 - 92 , 110 , the hip (3 studies) 43 , 50 , 85 , the ankle (1 study) 14 , and basic general arthroscopic skills (6 studies)…”
Section: Resultsmentioning
confidence: 99%
“…Several novel objective assessment tools have been developed and combine task-specific checklists with a global rating scale. The most promising front-runners among these are the Arthroscopic Surgical Skill Evaluation Tool (ASSET) 36 , 37 , 77 , which combines a task-specific checklist with an 8-domain global rating scale with end and middle descriptive anchors, and the Objective Structured Assessment of Technical Skills (OSATS) tool 23 , 93 (see Appendix Table 3). While the ASSET is obviously restricted to arthroscopic procedures, both have a growing body of evidence across all domains of the utility index (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…Each participant was determined to be competent if he or she achieved a final GRS score of competent or above, scored a minimum of 3 in each of the 8 ASSET subdomains as per the study by Koehler et al, 12 or achieved an ASSET score of 24 or greater. 6 No funding was received for this project. All implants and arthroscopic instruments were donated by Arthex.…”
Section: Methodsmentioning
confidence: 99%
“…The arthroscopic Bankart repair and the RCR were performed in the beach-chair or lateral position, again according to fellow preference. Fellows were assessed using a combination of task-specific checklists (previously validated in Sawbones models 14,15 ) and a GRS (the Arthroscopic Surgical Skill Evaluation Tool [ASSET]). 16,17 The ASSET GRS assesses skill in 7 domains on a scale of 1 to 5, with 1 representing novice performance, 3 representing competent performance and 5 representing expert performance: safety, field of view, camera dexterity, instrument dexterity, bimanual dexterity, the flow of the procedure, and the quality of the procedure.…”
Section: Intraoperative Assessmentmentioning
confidence: 99%
“…12,13,22,23 In orthopedics, studies using OSCEs have shown that residents progress over time in training with regard to their clinical knowledge and judgment 12 as well as the performance of technical skills on dry models. 14,15,24 However, previous research assessing the competence of orthopedic residents after a sports medicine rotation found that orthopedic residents were frequently not able to perform advanced arthroscopic procedures competently on dry models, despite focused training. 25 Although research continues to be published assessing competence in orthopedic technical skills using high-fidelity cadaveric models 23,26 and with virtual reality, 27 the assessment of technical skills in the operating room continues to pose challenges.…”
Section: E115mentioning
confidence: 99%